Strategi Pencegahan Bunuh Diri di Kalangan Pegawai Negeri pada Polri - Frans Tjahyono; Obing Katubi; Dini Rahma Bintari (Pusat Penelitian dan Pengembangan Polri, 2025)
The duty as a Civil Servant at the National Police (PNPP) is a job that has a high level of stress because you have to always deal with problems that exist in society. In the last year and a half, namely in 2022 there were 8 cases and in 2023, as of June 23, 2023, there have been 16 cases of police suicide. Data collection was carried out by distributing questionnaires to all PNPP in 34 Polda. FGD with key officials at Polda and Polres, as well as FGD with PNPP in the sample Polda. The results showed that from the results of filling out the Patient Health Questionnaire-9 (PHQ-9) questionnaire which was distributed to 34 Polda and Polres all over Indonesia, it could be concluded that 194 people were diagnosed with major depression and 428 people with moderate depression. The results of screening on mental health conditions, especially at Polda Metrojaya, identified members of the Satintelkam Airport Police who were diagnosed with depression and were finally committing suicide, so that this incident needs to be followed up immediately by all levels. Recommendations that can be used as an effort to improve suicide prevention patterns and strategies among PNPP are policy makers must provide attention and appropriate psychological intervention services to PNPP who The results of their mental health analysis show symptoms of depression, especially those in the category of moderate and severe, in the category of permissive/pro to suicide.